Funções musculares do assoalho pélvico em mulheres com e Sem incontinência urinária: apenas força e resistência são relevantes? - Gabriella Ferreira Vieira (2018)
INTRODUCTION: Urinary incontinence (UI) is the most prevalent pelvic floor dysfunction (PFD) among women and pelvic floor muscle training (PFMT) is the first line treatment for this population. The PFMT is focused on strength and endurance. However, some women would not benefit from this type of treatment once they present impairments of others pelvic floor muscle functions (PFMF), such as contraction capacity and coordination, compromising muscle ability to produce strength. Muscle functions are the "physiological functions of muscles" and are fundamental to human movement. These functions are interdependent and organized in a continuum. Therefore it is mandatory to understand not only strength and endurance, but also the other muscle functions, such as tone, reaction, contraction and relaxation capacity and coordination. The investigation of these functions will can guide the individualized, dose-specific and more effective physiotherapeutic intervention. AIMS: to document the potential impairments of all PFMF, in addition strength and endurance, in women with and without UI and to investigate the influence of these impairments on the occurrence of UI. METHODS: Cross-sectional observational study approved by the Universidade Federal de Minas Gerais (UFMG) ethics committee. Socio-demographic, clinical and PFMF data were collected among women with and without UI. The PFMF exam was performed using the Pelvic Floor Sensory and Muscular Functions Exam (EFSMAP), a valid and reliable exam. The presence and type of UI were documented through the International Consultation on Incontinence Questionnaire - Short Form (ICIQ-SF). Descriptive statistics characterized the sample on sociodemographic, clinical and PFMF data. The association between potential PFMF impairments and UI occurrence was tested by Logistic Regression in two models: a) inclusion of all PFMF; and b) inclusion of all but not strength and endurance. A level of 5% of significance was adopted. RESULTS: 208 women participated, 100 with IU and 108 without UI. Age (median and interquartile range) was 52.0 (42.2 - 63.0) and 43.0 (35.0-56.7) years for women with and without UI, respectively (p <0.001). Women with UI had a higher body mass index (p <0.001) and parity (p <0.001) than women without UI. The most frequent type of UI was mixed (54%), followed by stress UI (25%) and urge UI (21%). Symptoms of others PFD were found in both groups, more frequently in women with UI. All PFMF, except relaxation capacity, were associated with UI in the univariate analysis. In the multivariate models, as predicted, strength and endurance were strongly associated with UI. Reaction and coordination were identified as the most strongly PFMF associated with UI when strength and endurance were not tested. Both models were robust, they explained the occurrence of UI more than 60%. CONCLUSION: Strength and endurance are the PFMF that most influence the occurrence of UI, probably because they are the result of the most elementary functions, such as tone, reaction, contraction capacity and coordination. And these muscle functions are also identified as relevant for women with UI. Therefore all PFMF should be considered in the assesment and physiotherapeutic intervention of women with UI. These results provide a basis for prescription of a dose-specific PFMT contributing to a more effective physiotherapic treatment for women with UI.